Distributional Implications of Joint Tax Evasion - Odd Erik Nygård; Joel Slemrod; Thor Olav Thoresen (Center for Economic Studies and ifo Institute (CESifo), 2016)
Both buyers and sellers of goods and services may bene.t from letting their economic transactions go unrecorded for tax purposes. The supplier reduces his tax burden by underreporting income, whereas the consumer gains from buying a non-taxed lower-priced product. The distributional implications of such joint tax evasion depend on the amounts evaded, on where the evaders on both sides of the market are found in the income distribution and how the financial gain is split between the suppliers and demanders. We use various data sources to identify tax evasion among sellers and buyers of goods and services. Results clearly suggest that the tax-evasion-controlled estimate of income inequality in Norway exhibits more income dispersion than official estimates.
Keywords: D31; D63; H26; 330; tax evasion; income inequality; expenditure approach